2014
DOI: 10.1016/j.nicl.2014.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Brain putamen volume changes in newly-diagnosed patients with obstructive sleep apnea

Abstract: Obstructive sleep apnea (OSA) is accompanied by cognitive, motor, autonomic, learning, and affective abnormalities. The putamen serves several of these functions, especially motor and autonomic behaviors, but whether global and specific sub-regions of that structure are damaged is unclear. We assessed global and regional putamen volumes in 43 recently-diagnosed, treatment-naïve OSA (age, 46.4 ± 8.8 years; 31 male) and 61 control subjects (47.6 ± 8.8 years; 39 male) using high-resolution T1-weighted images coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
50
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 69 publications
3
50
0
Order By: Relevance
“…It has been previously suggested that a constellation of symptoms frequently encountered in OSA patients, such as depression, disturbances in attention, dysmetria of thought and affect, executive and verbal memory deficits [24][25][26], point to similarities with the spectra of two other well recognized neurological clinical syndromes, thalamocortical dysrhythmia and cerebellar cognitive affective syndrome [9,27,28]. Correspondingly, the neuroanatomical regions most commonly reported in clinical and animal studies as affected in OSA suggest that both the cerebellar modulation of neural circuits and the normal state-dependent flow of information between thalamus (and basal ganglia) and frontoparietal cortex are likely to be affected in susceptible patients [10,[29][30][31][32][33][34][35] (Fig. 1).…”
Section: The Neuropathology Of Obstructive Sleep Apneamentioning
confidence: 74%
“…It has been previously suggested that a constellation of symptoms frequently encountered in OSA patients, such as depression, disturbances in attention, dysmetria of thought and affect, executive and verbal memory deficits [24][25][26], point to similarities with the spectra of two other well recognized neurological clinical syndromes, thalamocortical dysrhythmia and cerebellar cognitive affective syndrome [9,27,28]. Correspondingly, the neuroanatomical regions most commonly reported in clinical and animal studies as affected in OSA suggest that both the cerebellar modulation of neural circuits and the normal state-dependent flow of information between thalamus (and basal ganglia) and frontoparietal cortex are likely to be affected in susceptible patients [10,[29][30][31][32][33][34][35] (Fig. 1).…”
Section: The Neuropathology Of Obstructive Sleep Apneamentioning
confidence: 74%
“…In addition, Brown et al revealed that the signal reduction in the putamen could be a symptom for multiple system atrophy and pure autonomic failure. Moreover, the putamen volume alteration was found in postural tachycardia, syndrome obstructive sleep apneoa and depression patients during a DARTEL‐VBM study, and a relationship between increased volume in the putamen and autonomic hyperactivity was confirmed . The menopausal transition is accompanied by a reduction in ovarian hormones, which plays an important role in autonomic control and homeostasis of the autonomic neural mechanisms .…”
Section: Discussionmentioning
confidence: 87%
“…; Kumar et al. , ). Thus, aberrant FC in OSA subjects may contribute to deficient autonomic regulation in the condition (Somers et al.…”
Section: Discussionmentioning
confidence: 99%
“…; Kumar et al. , ). Altered functional networks appeared in sensorimotor processing areas and may contribute to these functional impairments in the condition.…”
Section: Discussionmentioning
confidence: 99%